Pengaruh Work-Life Balance Dan Stres Kerja Terhadap Kinerja Karyawan Pada PT. Madonna Variakreasi Jakarta Selatan - Anjani Kusumaning Tyas; Syamsul Mu’arif (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
Abstract. This study aims to analyze the influence of work-life balance and job stress on employee performance at PT. Madonna Variakreasi, South Jakarta. This study used a quantitative method with a survey approach. The population in this study was all employees of PT. Madonna Variakreasi, South Jakarta, with a sample size of 51 respondents. Data collection was conducted through questionnaires, while data analysis techniques used validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination using SPSS. The results showed that work-life balance had a positive and significant effect on employee performance, with a calculated t-value of 12.920 > t-table 2.010 and a significance value of 0.000 < 0.05. Meanwhile, work stress did not significantly affect employee performance, with a calculated t-value of -0.525 < t-table 2.010 and a significance value of 0.602 > 0.05. Simultaneously, work-life balance and job stress significantly influence employee performance, with a calculated F-value of 88.337 > F-table 3.19 and a significance value of 0.000 < 0.05. The coefficient of determination (R²) is 0.781, meaning that 78.1% of the variation in employee performance can be explained by work-life balance and job stress, while the remaining 21.9% is influenced by other variables outside this study